(untitled) (Applied Biological Research, 2017)
Waterlogging is one of the serious constraints in maize production which affects crop growth and yield in low lying areas. In order to study the waterlogging tolerance in maize 60 line x tester crosses were evaluated during kharif 2014 and 2015 under non-stress and waterlogging-stress conditions. Thirteen selection indices including mean productivity (MP); geometric mean productivity (GMP); harmonic mean (HM); tolerance index (TOL); stress susceptibility index (SSI); stress tolerance index (STI); yield index (YI); yield stability index (YSI) and modified tolerance index under non-stress and stress condition (KiSTI) were calculated using yield in non-stress (YP) and stress condition (YS). The results showed that it was possible to identify superior combinations for waterlogging tolerance based on above stress indices. Indices STI, SSI, GMP, HM and YI were more accurate criteria for selection of waterlogging-tolerant and high yielding hybrids. Positive and significant correlation of MP, GMP, HM and STI with grain yield under both conditions revealed that these indices were more applicable and efficient for selection of waterlogging tolerant genotypes. On the basis of STI, GMP, HM YI and KiSTI WNCDMR11R1611 x LM-13, G24QC19-BBB-21-BBB × BML-6, WNCDMR11R1611 × HKI-163 and S99TLYQ-HG-AB*4-47-BBB × BML-7 proved most waterlogging tolerant hybrids and produced good yield under stress and non-stress conditions.